Analiza prenosa toplote v postopku sintranja feritov - Rek, Zlatko (Strojniški vestnik, 2002)
The paper deals with a heat-transfer analysis of the process of sintering ferrites in a furnace. Experimental measurements and a numerical simulations of the time development of the temperature field were performed. Due to the complexity of the problem the simulation had to be performed in two steps. The first step takes into consideration the whole furnace, while in the second step only a single ferite plate is analyzed. The experiment, the numerical model (the heat-transfer equation) and the generation of the discretized model of the furnace for the chosen computational domain e.g. furnaces with heaters plates, ferrites, bearers and supports, are described. The results of the numerical simulation are analyzed and compared with experimental data. The agreement between the numerical results and the experimental data was good.
Keywords: sintranje feritov; prenos toplote; simuliranje numerično; modeli sevanja; sintranje; feriti; simulacija